The Misrepresentation of Father-Daughter Incest in Neo-Victorianism on Screen: Misogynistic and Victim-Blaming Understandings of Gendered Violence in Penny Dreadful (2014-2016) - Pedro, Dina (Complutense Journal of English Studies, 2023)
Incest has traditionally been regarded as the universal taboo, despite its convoluted and changeable nature from period to period –both in the social and legal arenas (Tate 2013). As a result, incest has proven to be a fascinating topic for authors across history, particularly in the case of Victorian and neo-Victorian Gothic fiction. We can find copious examples of incestuous relationships in (neo-)Victorian literature and culture, whose representation aims 1) to question idealised conceptualisations of the nuclear family, 2) to denounce sexual and domestic violence against women and 3) to cater to the audience’s morbid fascination for these forbidden relationships (Llewellyn 2010; Cox 2014). Penny Dreadful is a neo-Victorian TV series that exploits incest to seemingly denounce patriarchal and sexual violence. However, as I show in this article, the (mis)representation of its female protagonists, Lily and Vanessa –as a misandrist woman and a femme fatale, respectively–, might mislead the audience into victim blaming them for their own downfalls, rather than acknowledge their status as survivors of gender-based violence. Therefore, in spite of the series’ apparent feminist drive, Penny Dreadful ends up reproducing patriarchal ideologies that blame and silence the victim and side with the perpetrator.